Biosynthesis of Selenium Nanoparticles Supported on and within Diatomite through a Continuous Flow Method - Luminița Dimitriu; Raluca Șomoghi; Daniel Preda; Diana Constantinescu-Aruxandei; Florin Oancea (Proceedings, 2020)
Diatomite, also known as diatomaceous earth (DE), is a sedimentary rock formed by the deposition of shells of unicellular microscopic algae of the class Bacillariophyceae (diatoms). [...]